Psychotherapeutic approaches to non-suicidal self-injury in adolescents - Washburn Jason J; Richardt Sarah L; Styer Denise M; Gebhardt Michelle; Juzwin K R; Yourek Adrienne; Aldridge Delia (BMC, 2012)
Abstract Non-suicidal self-injury (NSSI) among adolescents is gaining increasing attention in both clinical and scientific arenas. The lifetime prevalence of NSSI is estimated to vary between 7.5% to 8% for preadolescents, increasing to between 12% and 23% for adolescents. Despite the prevalence and the increasing interest in NSSI, few psychotherapeutic treatments have been designed specifically for NSSI, and no treatments have been evaluated specifically for the treatment of NSSI among adolescents. Consequently, child and adolescent clinicians are left with little evidence-based guidance for treating this challenging population. To provide some guidance, evaluations of treatments for adults with NSSI and for adolescents with related conditions, such as deliberate self-harm and borderline personality disorder, are reviewed. Clinical guidelines and resources are also discussed to assist with the gaps in the knowledge base for treatment of NSSI among adolescents.